ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL DIMENSI TIGA BERDASARKAN KATEGORI KESALAHAN MENURUT WATSON - Ai Rosita; Chandra Novtiar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the mistakes of vocational students in the Three Dimension material. This research was conducted in class XII students in one of the vocational schools in Cimahi as many as 26 students who were taken 6 random samples based on the results of the location of the mistakes made by students in different criteria according to Watson's error. The research approach used is qualitative descriptive method. The instrument used is a matter of validated mathematical bloom taxonomy. Tests conducted by students are examined for the type of error based on the Watson category and an analysis of the answer errors. The results showed that based on the percentage of the types of errors students who had solved mathematical problems based on the categories of errors according to Watson were incorrect data errors included in the small error of 13%, Procedure errors were not included in the very low error of 3%. Erroneous conclusions lost are included in the high error that is equal to 54%. Error in casting answers is 13%. While errors other than (above other / AO) or incorrect data writing and did not respond by 17%, included in the low error.